2011
DOI: 10.1152/ajpgi.00368.2010
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine modulation of cholangiocyte serotonin synthesis orchestrates biliary remodeling in adults

Abstract: Paracrine signaling between cholangiocytes and stromal cells regulates biliary remodeling. Cholangiocytes have neuroepithelial characteristics and serotonin receptor agonists inhibit their growth, but whether they are capable of serotonin biosynthesis is unknown. We hypothesized that cholangiocytes synthesize serotonin and that cross talk between liver myofibroblasts (MF) and cholangiocytes regulates this process to influence biliary remodeling. Transwell cultures of cholangiocytes ± MF, and tryptophan hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…Immunohistochemical staining to detect GLI2, SMO, αSMA, elastin, Krt19, SOX9, AFP, desmin, Ki67, and cyclin D1 was performed using the DAKO Envision System (DAKO Corporation) according to the manufacturer's protocol. Immunostaining were performed as described previously (69). Briefly, formalin-fixed paraffin-embedded liver tissues were cut into 5-μm sections and placed on glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining to detect GLI2, SMO, αSMA, elastin, Krt19, SOX9, AFP, desmin, Ki67, and cyclin D1 was performed using the DAKO Envision System (DAKO Corporation) according to the manufacturer's protocol. Immunostaining were performed as described previously (69). Briefly, formalin-fixed paraffin-embedded liver tissues were cut into 5-μm sections and placed on glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…Available data suggest in any case that 5-HT can sustain hepatocyte proliferation following PHX, likely by acting through a restrict number of receptors (5-HT1A, 2A and 2B), as also unequivocally indicated by the significant impairment of regeneration observed in Tph−/− mice [147,148]. Recently, it has proposed that cholangiocytes may represent an additional source of serotonin as resident liver cells, with serotonin that once released can in turn represses cholangiocyte proliferation through a negative feedback mechanism [149]. Interestingly, these Authors provided evidence suggesting that under conditions of biliary injury a peculiar cross-talk between cholangiocytes and MFs may occur, with 5-HT triggering TGFβ1 production by MFs (likely portal MFs) which, in turn, can act back on cholangiocytes to repress expression of tryptophan-hydroxylase 2 (TPH2, the enzyme generating serotonin) and enable their proliferation.…”
Section: Natural Killer and Natural Killer T Cells In Liver Fibrogenementioning
confidence: 96%
“…This suggests that a serotonin-mediated autocrine loop is capable of limiting biliary growth and subsequent ductular reaction during cholestasis. A recent study using tryptophan hydroxylase-2 knock-in (TPH2KI) mice demonstrated that serotonin is vital for remodeling injured bile ducts, and mice with reduced biliary serotonin levels exhibit excessive cholangiocyte proliferation, duct accumulation, and liver fibrosis following BDL 93 . The same study also demonstrated that serotonin stimulates myofibroblast production of TGF-β1, which decreases tryptophan hydroxylase-2 (TPH2) expression and subsequently decreases serotonin levels and its effects on cholangiocyte proliferation 93 .…”
Section: Mechanisms and Regulators Of Cholangiocyte Proliferationmentioning
confidence: 99%